Preparing future internal auditors for the digital age: An empirical assessment of skills, curriculum gaps, and professional expectations - Geqeza, Awonke (Edelweiss Applied Science and Technology, 2026)
The purpose of this paper is to examine how well South African universities prepare internal auditing graduates for a digitalized professional environment. Drawing on the Institute of Internal Auditors (IIA)’s competency guidance, national higher-education quality frameworks, and literature on 4IR and digital curricular transformation, the study employed a quantitative research approach. A questionnaire was administered to recent graduates, auditors, lecturers, and Chief Audit Executives (CAE), yielding 329 valid responses. The data was analyzed using reliability tests, exploratory factor analysis, and multiple linear regression in SPSS. Findings revealed that recent graduates are not ready for digitally operated institutions. This is consistent with gaps in data analytics, automation-aware evidence evaluation, cybersecurity awareness, and applied Artificial Intelligence (AI) audit skills. The paper concludes by recommending curriculum realignment to embed digital audit competencies, including data analytics, AI, cybersecurity, and automation. The study highlights the need for curriculum realignment, enhanced digital audit skills training, lecturer upskilling, stronger IIA–university collaboration, employer-led graduate development, and policy reforms to improve internal auditing graduates’ digital readiness in South Africa.